Catalyst for fuel cell as well as preparation method and application of catalyst

By using cerium-containing carbon support and platinum atoms in fuel cell catalysts in synergistic catalysis with non-precious metal core-shell structures, the problems of low utilization and poor stability of traditional catalysts are solved, and efficient and stable oxygen reduction reactions and cost-reducing effects are achieved. .

CN119208639APending Publication Date: 2024-12-27FAW JIEFANG AUTOMOTIVE CO
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411603074.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The utilization rate of platinum in traditional fuel cell catalysts is low and the stability is poor, the cost of precious metal platinum is high, and free radicals cause attacks on fuel cell modules, hindering its large-scale promotion and application.

Method used

An alloy layer containing cerium carbon support and a platinum atom and non-precious metal atom are used to synergistically catalyze the oxygen reduction activity through core-shell structure, and free radical attack is reduced through Ce elements to form an efficient and stable catalyst.

Benefits of technology

The oxygen reduction activity and stability of the catalyst are significantly improved, the amount of platinum is reduced, the service life of the fuel cell is extended, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208639A_ABST
    Figure CN119208639A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst for a fuel cell as well as a preparation method and application of the catalyst. The catalyst for the fuel cell comprises a cerium-containing carbon carrier and an alloy layer loaded on the cerium-containing carbon carrier, wherein the alloy layer comprises an alloy core of platinum atoms and non-noble metal atoms and a platinum shell coated on the surface of the alloy core. Synergistic catalysis exists between two active sites of the cerium-containing carbon carrier and the alloy layer composed of the platinum and the non-noble metal, and the oxygen reduction activity can be effectively improved; and on the other hand, due to the structural advantages of the core-shell structure catalyst, the dissolution of transition metal can be effectively inhibited, the stability is improved, and the attack of free radicals on each component of the fuel cell can be effectively reduced due to the existence of the Ce element of the carbon carrier, so that the catalyst shows relatively high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cell technology, and in particular to a catalyst for fuel cells and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cells have obvious advantages in the field of commercial vehicles and heavy trucks due to their zero pollution, long driving range, and excellent low temperature resistance. In the production of proton exchange membrane fuel cells (PEMFC), precious metal platinum (Pt) accounts for an important proportion of 40-60% of the cost.

[0003] Commercial platinum-on-carbon is currently the most effective catalyst for oxygen reduction reaction, but its high cost and poor stability have hindered its large-scale promotion and application. In addition, the utilization rate of platinum in traditional nanocatalysts is low, and only its surface is exposed to the electrolyte and only surface atoms participate in the electrocatalytic reaction. Therefore, a catalyst with high efficiency and stability is urgently needed. Summary of the invention

[0004] Based on this, the present application provides a fuel cell catalyst with high activity and stability, and a preparation method and application thereof.

[0005] The specific technical solutions are as follows:

[0006] The first aspect of the present application provides a catalyst for a fuel cell, comprising a cerium-containing carbon carrier and an alloy layer supported on the cerium-containing carbon carrier, wherein the alloy layer comprises an alloy core of platinum atoms and non-precious metal atoms and a platinum shell coated on the surface of the alloy core.

[0007] The catalyst of the present application includes a cerium-containing carbon carrier and an alloy layer loaded on the cerium-containing carbon carrier, and the alloy layer includes an alloy core of platinum atoms and non-precious metal atoms and a platinum shell coated on the surface of the alloy core. There is synergistic catalysis between the two active sites of the cerium-containing carbon carrier and the alloy layer composed of platinum and non-precious metals, which can effectively improve the activity of oxygen reduction; on the other hand, due to the structural advantages of the core-shell structure catalyst, the dissolution of transition metals can be effectively inhibited to improve stability, and the presence of Ce elements in the carbon carrier can effectively reduce the attack of free radicals on various components of the fuel cell, so the catalyst shows high stability.

[0008] In one embodiment, based on the total mass of the fuel cell catalyst, the mass fraction of platinum is 20% to 30%;

[0009] And / or, the mass fraction of cerium is 0.5% to 2%.

[0010] The second aspect of the present application provides a method for preparing the above-mentioned fuel cell catalyst, comprising the following steps:

[0011] A cerium source and a metal organic framework material precursor are mixed in a solvent, and a first pyrolysis and a first acid washing are performed in sequence to obtain a cerium-containing carbon support;

[0012] The cerium-containing carbon support, a non-precious metal source, and a platinum source are mixed in a solvent, and a second pyrolysis is performed to load alloy particles of the non-precious metal and platinum on the cerium-containing carbon support to obtain an intermediate;

[0013] The intermediate is subjected to a second acid wash to obtain the catalyst.

[0014] In one embodiment, the method for preparing the metal organic framework material precursor comprises:

[0015] Dimethylimidazole and zinc salt are mixed and reacted at 23° C. to 28° C. for 10 h to 14 h to prepare a metal organic framework material precursor.

[0016] In one embodiment, the mass ratio of the zinc salt, the cerium source and the dimethylimidazole is 1-5:0.1-0.2:2-3.

[0017] In one embodiment, the first pyrolysis condition is: in a protective gas, the temperature is increased to 700°C~1000°C at a heating rate of 2°C~10°C per minute, and the pyrolysis treatment is performed for 1h~4h.

[0018] In one of the embodiments, the mass volume ratio of the cerium-containing carbon support, the non-precious metal source and the platinum source is 0.1g~0.2g: 0.01g~0.02g: 0.6mL~0mL.

[0019] In one embodiment, the second pyrolysis condition is: in a protective gas, the temperature is increased to 600°C~800°C at a heating rate of 2°C~10°C per minute, and the pyrolysis treatment is performed for 1h~3h.

[0020] In one embodiment, the acid used in the second pickling includes at least one of nitric acid, sulfuric acid or acetic acid.

[0021] In a third aspect of the present application, a fuel cell is provided, wherein the fuel cell comprises a catalyst layer, and a raw material of the catalyst layer comprises the above-mentioned fuel cell catalyst or a fuel cell catalyst prepared by the above-mentioned method for preparing the fuel cell catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A schematic diagram of the reaction principle of a catalyst prepared in one embodiment of the present application;

[0023] Figure 2 OLSV comparison of comparative example 1 and example of the present application and XRD diagram of example 1;

[0024] Figure 3 This is the XRD diagram of Comparative Example 3 of the present application;

[0025] Figure 4 This is a transmission electron microscope image of Example 1 of the present application;

[0026] Figure 5 The polarization curves before and after durability of Example 1 of the present application;

[0027] Figure 6 The polarization curves before and after durability of Example 2 of the present application;

[0028] Figure 7 This is the polarization curve before and after durability of comparative example 2 of the present application;

[0029] Figure 8 This is the polarization curve of comparative example 3 of the present application before and after durability. DETAILED DESCRIPTION

[0030] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0031] The implementation of this application is described in detail below in combination with some implementation methods and examples. This example is implemented based on the technical solution of this application, and provides a detailed implementation method and specific operation process, but the protection scope of this application is not limited to the following examples.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0033] the term

[0034] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0035] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0036] In the present application, the terms "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0037] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0038] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0039] In this application, unless otherwise specified, the temperature parameter is allowed to be either a constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0040] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 2~5h means that the units of the left endpoint "2" and the right endpoint "5" are both h (hours).

[0041] As shown in the background technology, in the traditional technology, the utilization rate of platinum in fuel cell catalysts is low. Technicians have proposed that the core-shell catalyst can inhibit the loss of transition metals in the core layer because the shell layer is composed of a stable Pt atomic layer; on the other hand, the transition metals in the core layer of this structure can still play an electronic regulation role on the Pt atoms in the shell layer. This core-shell structure catalyst shows significantly improved activity and stability compared to traditional Pt / C catalysts; and due to the alloying of cheap transition metals, the amount of precious metal Pt can be significantly reduced, which effectively reduces the cost of the catalyst. Therefore, the Pt alloy catalyst with a core-shell structure has great development potential. Among them, the preparation of core-shell nano electrocatalysts mainly includes the following methods: a preparation method of a supported platinum-rhodium-copper alloy core-shell nano electrocatalyst includes mixing raw materials containing a platinum source, a copper source, and a rhodium source, a surfactant and an oleylamine solvent to obtain a mixed solution, heating the mixed solution to 160-280°C, reacting for 0.5-8 hours, and cooling; the cooled reaction solution is washed with acetic acid, and then centrifuged at a speed of not less than 8000r / min; the product platinum-rhodium-copper alloy nanoparticles whose surface does not contain a surfactant are obtained; the amount of acetic acid used is not less than the volume of the reaction solution; the obtained product and the platinum source are put into an oleylamine solvent, heated to react after mixing, cooled and centrifuged to obtain PtRhCu@Pt nanoparticles; the PtRhCu@Pt nanoparticles are mixed with a carbon carrier to obtain a PtRhCu@Pt catalyst. In another method for preparing a catalyst with high stability core-shell-shell structure oxygen reduction catalytic performance, hydrated yttrium (III) acetylacetonate and platinum (II) acetylacetonate are used in a hydrogen environment to prepare a Pd-Y-Pt / C core-shell-shell structure catalyst with Pd as the core, Y as the intermediate shell on the Pd particle and Pt as the outer shell. A method for preparing a composite carbon carrier PtCoRu catalyst comprises: (1) adding a carbon carrier to a mixed solution of deionized water and alcohol and stirring it into a carbon slurry, adding a cerium and tungsten precursor solution to the carbon slurry, and reducing it with a double reducing agent to obtain a W-Ce-C composite carbon carrier; (2) adding the composite carrier obtained in (1) to a mixed solution of DMF and alcohol and stirring it into a carbon slurry, then adding platinum, cobalt and a small amount of ruthenium precursor, and using a hydrothermal reaction to obtain a PtCoRu / W-Ce-C alloy catalyst.

[0042] However, the existing core-shell catalyst preparation process is often too complicated and requires high-temperature treatment. The complex process is not conducive to the large-scale preparation and commercialization of the catalyst, and high-temperature treatment often leads to the agglomeration growth of Pt nanoparticles, reducing the utilization rate of Pt; on the other hand, during the use of MNC carriers, free radicals will inevitably be generated. These groups with strong oxidizing ability will attack the proton exchange membrane and catalyst, reducing the output power of the fuel cell.

[0043] Based on this, one embodiment of the present application provides a catalyst for a fuel cell, comprising a cerium-containing carbon carrier and an alloy layer loaded on the cerium-containing carbon carrier, wherein the alloy layer comprises an alloy core of platinum atoms and non-precious metal atoms and a platinum shell coated on the surface of the alloy core.

[0044] The catalyst of the present application includes a cerium-containing carbon carrier and an alloy layer loaded on the cerium-containing carbon carrier, and the alloy layer includes an alloy core of platinum atoms and non-precious metal atoms and a platinum shell coated on the surface of the alloy core. There is synergistic catalysis between the two active sites of the cerium-containing carbon carrier and the alloy layer composed of platinum and non-precious metals, which can effectively improve the activity of oxygen reduction; on the other hand, due to the structural advantages of the core-shell structure catalyst, the dissolution of transition metals can be effectively inhibited to improve stability, and the presence of Ce elements in the carbon carrier can effectively reduce the attack of free radicals on various components of the fuel cell, so the catalyst shows high stability.

[0045] In some of the embodiments, based on the total mass of the fuel cell catalyst, the mass fraction of platinum is 20% to 30%, for example, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%.

[0046] In some of the embodiments, the mass fraction of cerium is 0.5% to 2%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%.

[0047] In some of the embodiments, the atomic ratio of platinum to the non-precious metal is 1-3:1, for example, 1:1, 3:1 or 2:1.

[0048] An embodiment of the present application provides a method for preparing a fuel cell catalyst, comprising steps S10 to S30.

[0049] Step S10: mixing a cerium source and a metal organic framework material precursor in a solvent, and performing a first pyrolysis and a first acid washing in sequence to obtain a cerium-containing carbon support.

[0050] Specifically, the method for preparing the metal organic framework material precursor comprises mixing dimethylimidazole and zinc salt, and reacting them at 23° C. to 28° C. for 10 h to 14 h to prepare the metal organic framework material precursor.

[0051] In some embodiments, the reaction temperature is 25° C. and the reaction time is 12 h.

[0052] In some embodiments, the metal organic framework material comprises ZIF-8.

[0053] It can be understood that the porous structure of ZIF-8 provides adsorption sites for the cerium source.

[0054] In some of the embodiments, the mass ratio of the zinc salt, the cerium source and the dimethylimidazole is 1-1.5:0.1-0.2:1.2-1.3, for example, it can be 1.16:0.18:1.232, 1.1:0.15:1.25 or 1.5:0.2:1.3.

[0055] In some of the embodiments, the preferred mass ratio of the zinc salt, the cerium source and the dimethylimidazole is in the range of 1.1-1.2:0.16-0.19:1.2-1.4.

[0056] Further controlling the mass ratio of the zinc salt, the cerium source and the dimethylimidazole within the above-mentioned ratio range can promote the formation of the MOF ZIF-8 and increase the doping content of the cerium source.

[0057] In some embodiments, the cerium source and dimethylimidazole are respectively placed in 10-40 mL of methanol solution and fully dispersed, and then mixed and stirred; the volume of the methanol solution includes but is not limited to 10 mL, 20 mL, 30 mL or 40 mL.

[0058] It can be understood that the cerium source can be dissolved in the methanol solution, so that it can be evenly mixed with the metal organic framework material precursor.

[0059] In some embodiments, the mixing and stirring time is 4 h to 7 h, for example, 4 h, 5 h, 6 h or 7 h.

[0060] In some of the embodiments, after the above-mentioned mixing step and before the above-mentioned first pyrolysis step, a vacuum drying treatment is also included at 30°C~80°C; for example, the vacuum drying temperature can be 30°C, 40°C, 50°C, 60°C, 70°C or 80°C.

[0061] In some embodiments, the conditions for the first pyrolysis are: in a protective gas, heating to 700°C~1000°C at a heating rate of 2°C~10°C per minute, and pyrolysis treatment for 1~4 hours; the pyrolysis temperature includes but is not limited to 700°C, 800°C, 900°C or 1000°C; the pyrolysis treatment time includes but is not limited to 1, 2, 3 or 4 hours; the heating rate includes but is not limited to 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0062] The cerium source is simultaneously reduced and dispersed on the carbon support in the form of single atoms through the first pyrolysis treatment. This is because high-temperature pyrolysis forms a strong interaction between the cerium atoms and the carbon support, preventing the agglomeration of the cerium atoms. The pyrolyzed sample is washed with acid to remove excess impurities and cerium agglomerates that have not formed single atomic sites, thereby obtaining a carbon support rich in cerium single atomic sites.

[0063] In some embodiments, the protective gas is a high-purity gas, and the protective gas includes at least one of nitrogen and argon.

[0064] The catalyst prepared in this application uses cerium as a carbon carrier, which can inhibit the generation of strong oxidizing groups, and can in situ convert OH radicals and OOH radicals into water, reducing the free radicals of strong oxidizing groups. On the one hand, this is conducive to improving the stability of the carbon carrier under high potential. Compared with commercial carbon carriers, the stability is improved by about 23% after 5000 cycles of accelerated durability.

[0065] Step S20: The cerium-containing carbon support, the non-precious metal source and the platinum source are mixed in a solvent, and a second pyrolysis is performed to load alloy particles of the non-precious metal and platinum on the cerium-containing carbon support to obtain an intermediate.

[0066] In some of the embodiments, the mass volume ratio of the cerium-containing carbon carrier, the non-precious metal source and the platinum source is 0.1~0.2g:0.01~0.02g:0.6~1.0ml, for example, it can be 0.1:0.01:0.6, 0.156:0.0164:0.825, 0.2:0.02:1.

[0067] In some of the embodiments, the preferred mass-to-volume ratio of the cerium-containing carbon support, the non-precious metal source, and the platinum source is in the range of 0.14-0.16 g: 0.015-0.018 g: 0.8-0.9 ml.

[0068] Further controlling the mass volume ratio of the cerium-containing carbon carrier, the non-precious metal source and the platinum source within the above-mentioned ratio range can promote the formation of the Pt3Co alloy, and control the mass fraction of Pt below 30%, which is beneficial to controlling the particle size of the alloy nanoparticles.

[0069] In some embodiments, the non-precious metal source includes a cobalt source.

[0070] During the above-mentioned mixed reaction process, Pt and Co ions are reduced and form Pt3Co alloy particles, which are deposited on the surface of the carbon support rich in Ce single atomic sites.

[0071] In some of the embodiments, the non-precious metal source and the cerium-containing carbon support are respectively placed in 5 mL to 30 mL of deionized water, fully dispersed, and then mixed and stirred; the volume of deionized water includes but is not limited to 5 mL, 10 mL, 20 mL or 30 mL.

[0072] In some embodiments, the mixing and stirring time is 8 h to 16 h, for example, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h or 16 h.

[0073] In some of the embodiments, after the mixing step and before the second pyrolysis step, a drying step is further included.

[0074] In some embodiments, the drying method includes at least one of drying and freeze drying.

[0075] In a specific example, the drying temperature is 60°C to 90°C, for example, 60°C, 70°C, 80°C or 90°C.

[0076] In another specific example, the freeze-drying treatment time is 10 h to 20 h, for example, 10 h, 15 h, 18 h or 20 h.

[0077] In some embodiments, the conditions for the second pyrolysis are: in a protective gas, heating to 600°C~800°C at a heating rate of 2°C~10°C per minute, and pyrolysis treatment for 1h~3h; the pyrolysis temperature includes but is not limited to 600°C, 700°C or 800°C; the pyrolysis treatment time includes but is not limited to 1h, 2h or 3h; the heating rate includes but is not limited to 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0078] The second pyrolysis treatment can form a Pt3Co alloy, which is the main active site of the catalyst.

[0079] In some embodiments, the protective gas is a high-purity gas, and the protective gas includes at least one of nitrogen and argon.

[0080] Step S30: subjecting the intermediate to a second acid wash to obtain the catalyst.

[0081] After the above treatment, Pt atoms form a Pt3Co core-shell structure catalyst on the surface of the Pt3Co core, while the Ce single atom site in the carbon carrier is still retained, thereby obtaining the target catalyst.

[0082] See also Figure 1 , Figure 1A schematic diagram of the principle of the core-shell catalyst reaction prepared for an embodiment of the present application. The above-mentioned Ce single atom site and the two active sites of the Pt3Co core-shell structure have an anchoring synergistic effect. On the one hand, the Pt3Co site can directly reduce hydrogen and oxygen to water, and on the other hand, the Ce single atom site can reduce hydrogen and oxygen to hydrogen peroxide, which is further reduced to water at the Pt3Co site. This synergistic effect can make full use of the surface area of ​​the carbon carrier, and at the same time can effectively improve the reduction efficiency of hydrogen and oxygen, significantly improving the mass activity and catalyst particle stability.

[0083] In some embodiments, the acid used in the second pickling includes at least one of nitric acid, sulfuric acid or acetic acid.

[0084] In a specific example, the acid used in the second pickling is nitric acid.

[0085] In some embodiments, the concentration of the acid used in the second acid wash is 0.1M-0.3M, for example, 0.1M, 0.2M or 0.3M.

[0086] In some embodiments, the pickling temperature is 60°C to 90°C, for example, 60°C, 70°C, 80°C or 90°C.

[0087] Through the second pickling treatment, a 2-3-layer Pt shell can be formed, which can inhibit the loss of Co element in the core layer Pt3Co alloy and improve durability.

[0088] In some of the embodiments, after the second acid washing step of the intermediate and before the step of preparing the catalyst, the process further includes the steps of successively filtering and drying the acid washed product.

[0089] In some of the embodiments, the filtrate used in the above-mentioned filtration process is a mixture of water and isopropanol, and the volume ratio of water to isopropanol is 0.5~2:0.5~2, for example, it can be 1:1, 0.5:1.5 or 1.5:0.5.

[0090] In some embodiments, the amount of the filtrate is 1L~3L, for example, 1L, 2L or 3L.

[0091] In some embodiments, the drying temperature is 40°C to 70°C, for example, 40°C, 50°C or 60°C.

[0092] In some embodiments, the drying time is 8 h to 16 h, for example, 8 h, 12 h or 16 h.

[0093] The present application provides a method for preparing a catalyst for a fuel cell, wherein a carbon carrier rich in single-atom distribution Ce is prepared by an impregnation pyrolysis method, and a catalyst is prepared based on the anchoring synergistic effect between the rich Ce single-atom sites of the carbon carrier and the two active sites of the core-shell structure of platinum atoms and non-precious metal atoms. On the one hand, the carrier of the present application is rich in Ce single-atom sites, and Ce is widely distributed on the surface of the carbon carrier, which can convert OH radicals and OOH radicals on the surface of the catalyst into water in situ, reduce the freeing of strong oxidizing free radicals, reduce the problem of proton exchange membranes and catalysts being easily attacked and deactivated by strong oxidizing free radicals during the operation of the fuel cell, and enhance the corrosion resistance of the carbon carrier and the chemical durability of the proton exchange membrane under start-stop, load addition and reduction, and cold start conditions. On the other hand, the intrinsic activity of Pt can be enhanced by the alloy synergistic effect and the core-shell structure, while suppressing the corrosion loss of internal transition metals to the outside, and improving the stability of nanoparticles. The preparation method adopts an impregnation preparation process, which is simple in process and easy to mass-produce. Compared with commercial catalysts, the mass activity of the catalyst is increased by about 26%, and the stability is increased by about 35% after 30,000 cycles of accelerated durability.

[0094] One embodiment of the present application further provides a fuel cell, wherein the fuel cell includes a catalyst layer, and a raw material of the catalyst layer includes the fuel cell catalyst or a fuel cell catalyst prepared by the method for preparing the fuel cell catalyst.

[0095] The above fuel cell has good electrochemical activity and high stability, long service life and low cost, and can be used in, but not limited to, automobiles, portable devices, and fixed power sources.

[0096] In some embodiments, the fuel cell is a proton exchange membrane fuel cell, which includes a proton exchange membrane, a catalyst layer, a gas diffusion layer and a bipolar plate.

[0097] The present application forms a core-shell structure with Pt as the shell and Pt3Co as the core through catalyst configuration design, and synergistically catalyzes with the Ce single atom sites rich in the carbon carrier to improve the catalyst activity; on the other hand, the Pt shell can inhibit the loss of the Co element in the internal core, and the Ce element can also reduce the attack of free radicals on the catalyst and membrane through anti-Fenton reaction, thereby improving the catalyst stability.

[0098] Through the CCM (catalytic layer) targeting technology, the ohmic polarization between the membrane electrode proton membrane, catalyst layer and gas diffusion layer is reduced, thereby improving the output current density of the membrane electrode; the membrane electrode technology containing hot melt adhesive sealing frame, CCM and gas diffusion layer is hot-pressed into one piece, which has the advantages of good batch consistency and high power density.

[0099] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0100] In order to better illustrate the present application, the contents of the present application are further described below in conjunction with embodiments.

[0101] Example 1

[0102] 1. Preparation of Carbon Supports Rich in Ce Single Atom Sites

[0103] (1) Place 1.16 g of Zn(NO3)2·6H2O and 0.18 g of Ce(NO3)3·6H2O metal sources in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform; place 1.232 g of dimethylimidazole in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform.

[0104] (2) Pour the above metal solution into dimethylimidazole solution and stir for 6 hours to form a suspension. The suspension is vacuum dried at 70°C for 12 hours to obtain a precursor.

[0105] (3) The dried precursor solid was subjected to the first pyrolysis in sequence under the protective gas of high-purity nitrogen, with a heating rate of 5°C / min, a pyrolysis temperature of 900°C, and a pyrolysis time of 2 h. The first acid washing was performed with 0.5 M HCl for 6 h and then filtered and dried to obtain a carbon carrier rich in Ce single atom sites.

[0106] 2. Preparation of intermediates

[0107] (1) Weigh 0.156 g of the Ce atom-rich carbon support prepared above and place it in 10 mL of deionized water and ultrasonically disperse it for 30 min until it is uniform. Weigh 0.825 mL of chloroplatinic acid solution (0.25 M in terms of Pt) and 0.0164 g of cobaltous chloride hexahydrate and place them in 10 mL of deionized water and ultrasonically disperse them for 30 min until they are uniform.

[0108] (2) Pour the above metal mixture into the carbon carrier mixture and stir for 12 h to obtain a fully dispersed suspension. Place the mixture on a heating table at 75 °C and control the rotation speed of the suspension magnet to 200 r / min. Wait for the deionized water to evaporate gradually until the sample becomes black and viscous. Then freeze-dry the product for 18 h.

[0109] (3) The sample obtained above was subjected to a second pyrolysis in a protective atmosphere with an argon-hydrogen ratio of 95:5, and heated to 700°C at a heating rate of 5°C / min for 3 hours to obtain an intermediate, which includes a Ce-containing carbon support and alloy particles loaded on the Ce-containing carbon support.

[0110] 3. Preparation of Pt3Co core-shell catalyst

[0111] (1) The intermediate obtained above was placed in a 0.25 M nitric acid solution for a second acid wash, and the ratio of nitric acid to catalyst was controlled to be 70 mL:0.246 g. The mixed solution was ultrasonically dispersed for 30 min until it was uniform, and then the acid wash temperature was controlled to be 80 ° C for 12 h.

[0112] (2) After the above pickling is completed, the suspension is washed with a mixture of water and isopropanol, the ratio of water to isopropanol is 1:1, and the amount of filtrate is controlled to be above 2L to ensure clean washing.

[0113] (3) The sample obtained by filtration was dried in an oven at 60° C. for 12 h to obtain a Pt3Co core-shell catalyst, which includes a Ce-containing carbon support and an alloy layer supported on the Ce-containing carbon support, wherein the alloy layer includes a Pt3Co alloy core and a platinum shell coated on the surface of the Pt3Co alloy core.

[0114] Example 2

[0115] The preparation method of the catalyst in Example 2 is basically the same as that in Example 1, except that the acid in the second acid wash is changed to 0.25M sulfuric acid.

[0116] The other steps and conditions are the same as those in Example 1.

[0117] Comparative Example 1

[0118] The difference between Comparative Example 1 and Example 1 is that no Ce(NO3)3·6H2O metal source is added during the preparation of the carbon carrier, specifically:

[0119] (1) Place 1.16 g of Zn(NO3)2·6H2O in 30 mL of methanol and disperse by ultrasonic for 30 min until uniform; place 1.232 g of dimethylimidazole in 30 mL of methanol and disperse by ultrasonic for 30 min until uniform.

[0120] (2) Stirring for 6 h to form a suspension, and vacuum drying the suspension at 70 °C for 12 h to obtain a precursor.

[0121] (3) The dried precursor solid was subjected to a first pyrolysis in the protective gas of high-purity nitrogen, with a heating rate of 5°C / min, a pyrolysis temperature of 900°C, and a pyrolysis time of 2 h. The first acid washing was performed with 0.5 M HCl for 6 h and then filtered and dried to obtain a carbon support.

[0122] Comparative Example 2

[0123] The preparation methods of the catalysts in Comparative Example 2 and Example 1 are basically the same, except that cobaltous chloride hexahydrate is not added during the catalyst preparation process.

[0124] Specifically: 1. Preparation of carbon carriers rich in Ce single atom sites

[0125] (1) Place 1.16 g of Zn(NO3)2·6H2O and 0.18 g of Ce(NO3)3·6H2O metal sources in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform; place 1.232 g of dimethylimidazole in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform.

[0126] (2) Pour the above metal solution into dimethylimidazole solution and stir for 6 hours to form a suspension. The suspension is vacuum dried at 70°C for 12 hours to obtain a precursor.

[0127] (3) The dried precursor solid was subjected to the first pyrolysis in the protective gas of high-purity nitrogen, with a heating rate of 5°C / min, a pyrolysis temperature of 900°C, and a pyrolysis time of 2 h. The first acid washing was performed with 0.5 M HCl for 6 h and then filtered and dried to obtain a carbon carrier rich in Ce single atom sites.

[0128] 2. Preparation of intermediates

[0129] (1) Weigh 0.156 g of the Ce atom-rich carbon support prepared above and place it in 10 ml of deionized water and ultrasonically disperse it for 30 min until it is uniform. Weigh 0.825 ml of chloroplatinic acid solution (0.25 M in terms of Pt) and place it in 10 ml of deionized water and ultrasonically disperse it for 30 min until it is uniform.

[0130] (2) Pour the above metal mixture into the carbon carrier mixture and stir for 12 h to obtain a fully dispersed suspension. Place the mixture on a heating table at 75 °C and control the rotation speed of the suspension magnet to 200 r / min. Wait for the deionized water to evaporate gradually until the sample becomes black and viscous. Then freeze-dry the product for 18 h.

[0131] (3) The sample obtained above was subjected to a second pyrolysis in a protective atmosphere with an argon-hydrogen ratio of 95:5, and heated to 700°C at a heating rate of 5°C / min for 3 hours to obtain an intermediate, which includes a Ce-containing carbon support and platinum particles loaded on the Ce-containing carbon support.

[0132] Comparative Example 3

[0133] The preparation method of the catalyst in Comparative Example 3 is basically the same as that in Example 1, except that the preparation of the Pt3Co core-shell structure is not performed.

[0134] Specifically: 1. Preparation of carbon carriers rich in Ce single atom sites

[0135] (1) Place 1.16 g of Zn(NO3)2·6H2O and 0.18 g of Ce(NO3)3·6H2O metal sources in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform; place 1.232 g of dimethylimidazole in 30 mL of methanol and disperse them by ultrasonic for 30 min until they are uniform.

[0136] (2) Pour the above metal solution into dimethylimidazole solution and stir for 6 hours to form a suspension. The suspension is vacuum dried at 70°C for 12 hours to obtain a precursor.

[0137] (3) The dried precursor solid was subjected to the first pyrolysis in sequence under the protective gas of high-purity nitrogen, with a heating rate of 5°C / min, a pyrolysis temperature of 900°C, and a pyrolysis time of 2 h. The first acid washing was performed with 0.5 M HCl for 6 h and then filtered and dried to obtain a carbon carrier rich in Ce single atom sites.

[0138] 2. Preparation of intermediates

[0139] (1) Weigh 0.156 g of the Ce atom-rich carbon support prepared above and place it in 10 ml of deionized water and ultrasonically disperse it for 30 min until it is uniform. Weigh 0.825 ml of chloroplatinic acid solution (0.25 M in terms of Pt) and 0.0164 g of cobaltous chloride hexahydrate and place them in 10 ml of deionized water and ultrasonically disperse them for 30 min until they are uniform.

[0140] (2) Pour the above metal mixture into the carbon carrier mixture and stir for 12 h to obtain a fully dispersed suspension. Place the mixture on a heating table at 75 °C and control the rotation speed of the suspension magnet to 200 r / min. Wait for the deionized water to evaporate gradually until the sample becomes black and viscous. Then freeze-dry the product for 18 h.

[0141] (3) The sample obtained above was subjected to a second pyrolysis in a protective atmosphere with an argon-hydrogen ratio of 95:5, and heated to 700°C at a heating rate of 5°C / min for 3 hours to obtain an intermediate, which includes a Ce-containing carbon support and alloy particles loaded on the Ce-containing carbon support.

[0142] Performance Testing

[0143] The samples prepared in the above embodiments and comparative examples were subjected to the following tests:

[0144] (1) Microstructure observation was performed using a scanning electron microscope.

[0145] (2) Use X-ray diffractometer to test purity and crystallinity.

[0146] (3) Initial ORR activity test: battery temperature 85℃, active area 25cm2, H2 / O2 flow into anode and cathode respectively, flow rate An / Ca: 2 / 4 NLPM, back pressure anode / cathode: 50 / 50 kPag, anode and cathode both 100% humidified, maintained at 0 A / cm2 for 2 min, 1000, 200, 100, 80, 60, 40, 20 mA / cm2 for 15 min each, 10, 6, 4, 2 mA / cm2 for 5 min each. According to the current-voltage curve under H2 / O2 conditions (with mass current density as the horizontal axis), the mass specific activity (A / mg Pt@0.9 V) can be obtained by taking the current value at 0.9 V.

[0147] (4) Catalyst accelerated durability test: battery temperature 85°C, active area 25cm 2 100% humidified nitrogen and hydrogen were introduced into the cathode and anode, with flow rates of 75 sccm and 200 sccm respectively, and the outlet back pressure was 0 kPag. The operating potential was 0.6-0.95 V, square wave cycle, and the battery polarization curve was tested at 30,000 cycles.

[0148] (5) Catalyst carrier accelerated durability test: battery temperature 80°C, active area 25cm 2 100% humidified nitrogen and hydrogen were introduced into the cathode and anode, with flow rates of 75 sccm and 200 sccm respectively, and the outlet back pressure was 0 kPag. The operating potential was 1.0-1.5V triangle wave cycle, and the battery polarization curve was tested at 5000 cycles. The results are shown in Table 1.

[0149] Table 1

[0150]

[0151] from Figure 2From the OLSV curve, the Ce-containing carbon support in Example 1 shows obvious ORR activity compared with that in Comparative Example 1. At the same time, the metal crystallization peak of Example 1 is not found in the XRD curve, which indicates that the Ce in Example 1 exists in the form of single atoms and can act as an ORR active site. Compared with Comparative Example 1, Example 1 increases the utilization rate of the carbon support surface.

[0152] from Figure 3 From the XRD diagram of comparative example 3, it can be seen that the crystallization peak of comparative example 3 corresponds well to the standard card of Pt3Co, which indicates that the Pt3Co of comparative example 3 has good crystallinity and explains the successful synthesis of the Pt3Co alloy. Figure 4 It can be seen from the transmission electron microscopy image of Example 1 that after acid washing, the nanoparticles of the catalyst become a core-shell structure with Pt as the shell and Pt3Co as the core. This structure is beneficial for inhibiting the dissolution of transition metals while ensuring the alloy effect.

[0153] Figure 5 As shown, the mass activity of the catalyst in Example 1 of the present application can reach more than 501 mA / mgPt@0.90V, and the mass activity can reach more than 350.7 mA / mgPt@0.90V after 30,000 cycles of accelerated durability. Its mass activity decay is only about 30%, which is better than the 20% JM commercial Pt / C catalyst commonly used on the market. The initial mass activity of this commercial catalyst is 200mA / mgPt@0.90V, and the mass activity decays by 50% after 30,000 cycles of accelerated durability.

[0154] Figure 6 As shown, the initial mass activity of Example 2 of the present application is 400mA / mgPt@0.90, and 300.3mA / mgPt@0.90 after durability. The performance difference between Example 2 and Example 1 lies in the type of acid used in pickling, which indicates that the nitric acid pickling provided in the present application can effectively improve the activity and durability of the catalyst.

[0155] Figure 7 As shown, the initial mass activity of comparative example 2 of the present application is 250 mA / mgPt@0.90, and 117.2 mA / mgPt@0.90 after durability. The performance difference between comparative example 2 and example 1 lies in whether there is alloying of Co source. Combining the polarization curves of comparative example 2 and example 1, it can be concluded that the Pt3Co alloying technology provided in the present application can effectively improve the activity and durability of the catalyst.

[0156] Figure 8As shown, the initial mass activity of comparative example 3 of the present application is 450mA / mgPt@0.90, and 330.2mA / mgPt@0.90V after durability. The performance difference between comparative example 3 and embodiment 1 lies in whether Pt3Co has a core-shell structure, which indicates that the core-shell structure technical solution provided in the present application can effectively improve the activity and durability of the alloy catalyst and can meet the practical application of fuel cells.

[0157] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0158] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A catalyst for a fuel cell, characterized in that: The invention comprises a cerium-containing carbon carrier and an alloy layer loaded on the cerium-containing carbon carrier. The alloy layer comprises an alloy core of platinum atoms and non-noble metal atoms and a platinum shell covering the surface of the alloy core.

2. The fuel cell catalyst according to claim 1, wherein Based on the total mass of the fuel cell catalyst, the mass fraction of platinum is 20% to 30%; And / or, the mass fraction of cerium is 0.5% to 2%.

3. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: The steps include: A cerium source and a metal organic framework material precursor are mixed in a solvent, and a first pyrolysis and a first acid washing are performed in sequence to obtain a cerium-containing carbon support; The cerium-containing carbon support, a non-precious metal source, and a platinum source are mixed in a solvent, and a second pyrolysis is performed to load alloy particles of the non-precious metal and platinum on the cerium-containing carbon support to obtain an intermediate; The intermediate is subjected to a second acid wash to obtain the catalyst.

4. The method for preparing a fuel cell catalyst according to claim 3, wherein: The method for preparing the metal organic framework material precursor comprises: Dimethylimidazole and zinc salt are mixed and reacted at 23° C. to 28° C. for 10 h to 14 h to prepare a metal organic framework material precursor.

5. The method for preparing a fuel cell catalyst according to claim 4, characterized in that: The mass ratio of the zinc salt, the cerium source and the dimethylimidazole is 1-1.5:0.1-0.2:1.2-1.

3.

6. The method for preparing a fuel cell catalyst according to any one of claims 3 to 5, characterized in that: The first pyrolysis condition is: in a protective gas, the temperature is raised to 700° C. to 1000° C. at a heating rate of 2° C. to 10° C. per minute, and the pyrolysis treatment is performed for 1 hour to 4 hours.

7. The method for preparing a fuel cell catalyst according to any one of claims 3 to 5, characterized in that: The mass volume ratio of the cerium-containing carbon support, the non-precious metal source and the platinum source is 0.1 g~0.2 g: 0.01 g~0.02 g: 0.6 mL~1.0 mL.

8. The method for preparing a fuel cell catalyst according to any one of claims 3 to 5, characterized in that: The second pyrolysis condition is: in a protective gas, the temperature is increased to 600° C. to 800° C. at a heating rate of 2° C. to 10° C. per minute, and the pyrolysis treatment is performed for 1 hour to 3 hours.

9. The method for preparing a fuel cell catalyst according to any one of claims 3 to 5, characterized in that: The acid used in the second pickling includes at least one of nitric acid, sulfuric acid or acetic acid.

10. A fuel cell, characterized in that: The fuel cell comprises a catalyst layer, and the raw material of the catalyst layer comprises the fuel cell catalyst according to any one of claims 1 to 2 or the fuel cell catalyst prepared by the method for preparing the fuel cell catalyst according to any one of claims 3 to 9.

Citation Information

Cited By

  • Cerium oxide controllably modified noble metal-based porous carbon catalyst, preparation method and application

    CN119786623A